Environmental controllers for carbon emission and concentration patterns in Siberian rivers during different seasons - Kritskov, Ivan V.; Lim, Artem G.; Shirokova, Liudmila S.; Korets, Mikhail A.; Karlsson, Jan; Pokrovsky, Oleg S. (Science of the total environment)
Despite the importance of small and medium size rivers of Siberian boreal zone in greenhouse gases (GHG) emission, major knowledge gaps exist regarding its temporal variability and controlling mechanisms. Here we sampled 11 pristine rivers of the southern taiga biome (western Siberia Lowland, WSL), ranging in watershed area from 0.8 to 119,000 km2, to reveal temporal pattern and examine main environmental controllers of GHG emissions from the river water surfaces. Floating chamber measurements demonstrated that CO2 emissions from water surface decreased by 2 to 4-folds from spring to summer and autumn, were independent of the size of the watershed and stream order and did not exhibit sizable (>30 %, regardless of season) variations between day and night. The CH4 concentrations and fluxes increased in the order “spring ≤ summer < autumn” and ranged from 1 to 15 μmol L−1 and 5 to 100 mmol m−2 d−1, respectively. The CO2 concentrations and fluxes (range from 100 to 400 μmol L−1 and 1 to 4 g C m−2 d−1, respectively) were positively correlated with dissolved and particulate organic carbon, total nitrogen and bacterial number of the water column. The CH4 concentrations and fluxes were positively correlated with phosphate and ammonia concentrations. Of the landscape parameters, positive correlations were detected between riparian vegetation biomass and CO2 and CH4 concentrations. Over the six-month open-water period, areal emissions of C (>99.5 % CO2; <0.5 % CH4) from the watersheds of 11 rivers were equal to the total downstream C export in this part of the WSL. Based on correlations between environmental controllers (watershed land cover and the water column parameters), we hypothesize that the fluxes are largely driven by riverine mineralization of terrestrial dissolved and particulate OC, coupled with respiration at the river bottom and riparian sediments. It follows that, under climate warming scenario, most significant changes in GHG regimes of western Siberian rivers located in permafrost-free zone may occur due to changes in the riparian zone vegetation and water coverage of the floodplains.